Pilot Study Assessing the Use of High-density Polyethylene (Su-Por) for Tube Shunt Patch Grafts. Issue 1 (January 2018) - Abramowitz, Benjamin; Moster, Marlene R.; Pro, Michael; Schmidt, Courtland; Dale, Elizabeth; Yung, Edward; Williams, Alice
Abstract : Purpose: To assess the viability of a manufactured high-density polyethylene patch graft material (Su-Por) for prevention of tube shunt exposure. Materials and Methods: Retrospective review of the first 11 patients from the Wills Eye Hospital Glaucoma Service to receive the high-density polyethylene patch graft during tube shunt surgery. Results: Four patients (36.3%) experienced an extrusion of the Su-Por patch without a leak within 2.5 months of postoperative follow-up. All 4 patients developed either symptomatic or progressive extrusion. Operative repair was completed with Su-Por removal and replacement with a new human donor patch graft. No patient developed any sign of infection despite the extrusions. The remaining 7 patients had an uneventful postoperative course and continue to have no complications from the Su-Por patch with 9 months of follow-up. Conclusions: Given the high rate of extrusion of the Su-Por graft, this material seems to be an inadequate alternative for covering tube shunts. Harvested human tissue or other more flexible, manufactured grafts remain the standard of care for covering tube shunts.